Point of care hemoglobin testing in plateletpheresis donors: Noninvasive versus invasive methods - Mallhi, R.S. (Med J Armed Forces India, 2016)
BACKGROUND: Predonation hemoglobin (Hb) for plateletpheresis donors is estimated by presently available invasive methods. Venous samples of only those donors whose Hb is more than 12.5 g/dl are screened for complete blood count and transfusion transmissible infections. There is a pressing need to substitute this invasive Hb test with noninvasive one to reduce donor discomfort and avoid further pricking the donor. We therefore went ahead with the aim of comparing a noninvasive Hb estimation method NBM 200 with the invasive method – Hemocue, taking SYSMEX KX-21 as a gold standard. METHODS: 500 voluntary consenting plateletpheresis donors qualifying the laid down criteria for platelet donation were included in the study. Hb readings obtained by the NBM 200 and Hemocue were compared to those obtained from the fully automated hematology analyzer SYSMEX KX-21. RESULTS: Coefficients of correlation were found to be statistically significant at <0.0001 level of confidence. Results of Friedman's test on the three methods also showed significant difference in means. Bland–Altman plots and mountain plots also confirm the same. NBM 200 was found to be more sensitive, specific, and precise than Hemocue in detecting ineligible donors. CONCLUSION: NBM 200 was found to be more sensitive, specific, and precise as compared to Hemocue for predonation screening of Hb in plateletpheresis donors and the prime benefit it offers is that it is ‘noninvasive’ thereby assisting in stemming the platelet donor pool. The onus lies on the blood transfusion services to make use of appropriately validated gadgets that reduce the donor discomfort.